Schenkerian Analysis - Analyse nach Heinrich Schenker - Schwab-Felisch, Oliver,; Polth, Michael,; Fladt, Hartmut, (Georg Olms Verlag, 2021)
There are two main reasons why Heinrich Schenker became one of the most discussed music theorists of the 20th century: Firstly, his theory enables descriptions of the voice leading, harmony and syntax of tonal works that are as multi-layered as they are consistent. And secondly, Schenker's 'theory of layers' found ideal conditions in the USA, where most of Schenker's students had emigrated after 1933 - conditions that quickly allowed it to rise to become the leading theory of tonal music. In Austria, Germany and Switzerland, Schenker's reception initially took a different path: until the turn of the millennium, Schenker's theory remained the preserve of a few specialists. Since then, however, it has also met with growing interest in the German-speaking world. This German-English anthology contributes to Schenker research in both language areas and academic cultures. It examines questions of theoretical history, illuminates unexplored aspects of Schenker theory and opens up numerous of its implications for the theory of science, the history of reception and music aesthetics. In doing so, he often goes beyond Schenker - through new ideas of rhythm and metrics, references to Niklas Luhmann's systems theory or pluralistic theoretical concepts. The separate music volume contains analytical graphics as well as original musical texts. Online audio examples illustrate how different analytical interpretations can affect musical performances. Finally, a glossary and index facilitate in-depth readings along the lines of specific questions. A fundamental study book that shows music theorists and performers numerous possibilities for being inspired by Schenker's thinking.